Interaction between different sports branches such as taekwondo, box, athletes and serum brain derived neurotrophic factor levels - Oztasyonar, Y. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: This study aimed to compare serum brain-derived neurotrophic factor (BDNF) levels "which contributes in both neuron development/regeneration" between combat sport braches, which requires high attention and concentration and can lead micro and macro brain trauma, and athleticism, which requires durability in competition.